2009
DOI: 10.1038/ni.1798
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA miR-326 regulates TH-17 differentiation and is associated with the pathogenesis of multiple sclerosis

Abstract: Interleukin 17 (IL-17)-producing T helper cells (T(H)-17 cells) are increasingly recognized as key participants in various autoimmune diseases, including multiple sclerosis. Although sets of transcription factors and cytokines are known to regulate T(H)-17 differentiation, the role of noncoding RNA is poorly understood. Here we identify a T(H)-17 cell-associated microRNA, miR-326, whose expression was highly correlated with disease severity in patients with multiple sclerosis and mice with experimental autoimm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
554
1
16

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 722 publications
(590 citation statements)
references
References 41 publications
19
554
1
16
Order By: Relevance
“…As such, these miRNAs may be differentially expressed in other immunemediated diseases and have broader implications on CD4 T cell development and differentiation. It is well established that miRNAs play key roles in the development and function of Tregs (Gao et al, 2012;Josefowicz et al, 2012;Dooley et al, 2013), and differential expression of miRNAs have been found in patients with multiple sclerosis (Du et al, 2009;Keller et al, 2009;Otaegui et al, 2009;De Santis et al, 2010;Guerau-de-Arellano et al, 2011;Noorbakhsh et al, 2011;Jr OeF et al, 2012;Smith et al, 2012;Gandhi et al, 2013;Ridolfi et al, 2013;Søndergaard et al, 2013). To our knowledge none of the miRNAs identified in this study had been previously defined to play a role in Tregs.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…As such, these miRNAs may be differentially expressed in other immunemediated diseases and have broader implications on CD4 T cell development and differentiation. It is well established that miRNAs play key roles in the development and function of Tregs (Gao et al, 2012;Josefowicz et al, 2012;Dooley et al, 2013), and differential expression of miRNAs have been found in patients with multiple sclerosis (Du et al, 2009;Keller et al, 2009;Otaegui et al, 2009;De Santis et al, 2010;Guerau-de-Arellano et al, 2011;Noorbakhsh et al, 2011;Jr OeF et al, 2012;Smith et al, 2012;Gandhi et al, 2013;Ridolfi et al, 2013;Søndergaard et al, 2013). To our knowledge none of the miRNAs identified in this study had been previously defined to play a role in Tregs.…”
Section: Discussionmentioning
confidence: 63%
“…While genetic studies have identified genes critical to the immune system as being potential risk factors (Baranzini et al, 2009b;De Jager et al, 2009;Beecham et al, 2013), many of the genetic contributors to this disease are unknown. An emerging area of interest in multiple sclerosis has been genetic regulation at the microRNA (miRNA) level (Du et al, 2009;Keller et al, 2009;Otaegui et al, 2009;De Santis et al, 2010;Guerau-de-Arellano et al, 2011;Noorbakhsh et al, 2011;Jr OeF et al, 2012;Smith et al, 2012;Gandhi et al, 2013;Ridolfi et al, 2013;Søndergaard et al, 2013). MiRNAs are small, non-coding RNA that regulate gene expression and, thus, modify cellular pathways and disease processes (Ambros, 2004;Bartel, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Naive CD4ϩCD44Ϫ CD62Lϩ T cells were activated with anti-CD3 mAb (5 g/ml) and anti-CD28 mAb (2 g/ml) and were induced to differentiation according to the method described by Du et al, with slight modification (29). For Th1 cell differentiation, murine IL-12 (mIL-12; 10 ng/ml [Peprotech]) and anti-mIL-4 (10 g/ml; BD PharMingen) were added to the cultures; for Th2 cell differentiation, mIL-4 (40 ng/ml; eBioscience) and antimurine IFN␥ (anti-mIFN␥; 10 g/ml [eBioscience]) were added to the cultures; for inducible Treg cell differentiation, human transforming growth factor ␤1 (hTGF␤1; 10 ng/ml [Peprotech]) and mIL-2 (100 units/ml; BD PharMingen) plus anti-mIFN␥ (10 g/ml) were added to the cultures.…”
Section: Methodsmentioning
confidence: 99%
“…Naïve CD4 1 T cells were isolated and then polarized to Th17 lineage in the presence of SAHA or DMSO as previously described. 32 Flow cytometry analysis of polarized T cells revealed that SAHA significantly suppressed the production of Th17 cells (Figure 3b), and western blot analysis indicated that SAHA reduced the expression of RORct and STAT3, and by which it promoted Foxp3 expression (Figure 3c). In line with these results, qPCR analysis further confirmed that SAHA downregulated the expression of IL-17A, IL-17F, STAT3 and RORct, but upregulated Foxp3 and CTLA-4 expressions (Figure 3d).…”
Section: Saha Prolongs the Survival Time Of Murine Cardiac Allograftsmentioning
confidence: 97%